Local immunosuppression in vascularized composite allotransplantation (VCA): a systematic review - Safi, Ali-Farid; Kauke-Navarro, Martin; Nelms, Laurel; Palmer, William Jackson; Tchiloemba, Bianief; Kollar, Branislav; Haug, Valentin; Pomahač, Bohdan (Journal of plastic, reconstructive & aesthetic surgery, 2021)
Background - Local immunosuppression in vascularized composite allotransplantation (VCA) aims to minimize immunosuppressant-related toxic and malignant side effects. Promising allograft survival data have been published by multiple workgroups. In this systematic review, we examine preclinical animal studies that investigated local immunosuppression in VCA. - Material and methods - We conducted a systematic review of manuscripts listed in the MEDLINE and PubMed database concerning preclinical VCA models. Papers included had to be available as full-text and written in English. Non-VCA studies, human trials, and studies using cell-based therapy strategies were excluded. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. - Results - Literature research retrieved 980 articles. Ten studies published between 2010 and 2019 met the inclusion and exclusion criteria. Seven out of ten articles demonstrated a significant prolongation of allograft survival by using local immunosuppression. Five articles employed tacrolimus (TAC) as the main immunosuppressive agent. Seven studies performed hind-limb VCA in a rat model. - Conclusion - The easily accessible location of skin containing VCAs makes it an ideal candidate for local immunosuppression. Published preclinical data are very promising in terms of improved allograft survival and reduced systemic toxicity.